Fatty acid oxidation disorders as primary cause of sudden and unexpected death in infants and young children: an investigation performed on cultured fibroblasts from 79 children who died aged between 0-4 years. Issue 4 (August 1997) - Lundemose, J B; Kølvraa, S; Gregersen, N; Christensen, E; Gregersen, M
Abstract : BACKGROUND: Disorders of fatty acid metabolism are known to be responsible for cases of sudden and unexpected death in infancy. At least 14 disorders are known at present. 120 cases of sudden infant death syndrome (SIDS) had been examined for a prevalent mutation (G985) causing medium chain acyl CoA dehydrogenase deficiency, which is inherited in an autosomal recessive mode. No over-representation of either homozygous or heterozygous cases was found. AIMS: To investigate a broader spectrum of fatty acid oxidation disorders in a wider range of sudden deaths in infants and young children. METHODS: Seventy nine cases of unexpected death in infants and young children younger than 4 years old were examined for a minimum of nine fatty acid oxidation disorders, using the global [9, 10-3H] myristic acid oxidation assay in cultured fibroblasts from achilles tendon biopsies taken at postmortem examination. RESULTS: Three cases with fatty acid oxidation disorders and two carriers of the G985 mutation were found, all categorized as non-SIDS or borderline SIDS. The global assay used has the advantage of simplicity. CONCLUSIONS: These results indicate that disorders of fatty acid oxidation play a small but significant role in the cause of unexpected death in infants and young children, and that infants and children dying in this way should be regarded as high risk candidates for metabolic diseases.